Quizizz for EFL Learning Tool: Students’ Views and Attitudes - Sorohiti Maryam; Nadra Adyra Yasa Nauli; Suryanto Jati; Fatimah Nur (SHS Web of Conferences)
As technology-based educational tools become increasingly prevalent in global educational settings, it is essential for teaching methods to evolve alongside technological advancements to maintain students’ engagement. Quizizz, a notable platform within Mobile Assisted Language Learning (MALL), has been widely adopted by English educators to enhance the teaching and learning experience. This study aimed to explore students’ perspectives on utilizing Quizizz as a learning tool and identify the primary aspect of their attitudes toward its use. Employing a quantitative research approach with a survey design, data was gathered from 79 students enrolled in the English Department of a university in Indonesia. Results indicated that students generally hold positive attitudes toward Quizizz, with an overall mean score of 3.25 for students’ attitude (M = 3.25). Furthermore, the affective aspect emerged as the most prominent facet, showing the highest mean score of 3.29 (M = 3.29). The findings suggested that Quizizz is favoured among students for its ability to enhance motivation, engagement, and memorization. This study underscored the recommendation to integrate Quizizz into language learning and teaching practices.